Mapping our heritage: towards a sustainable future for digital spatial information and technologies in European archaeological heritage management - Green, C; Verhagen, P; McKeague, P; Van'T Veer, R; Huvila, I; Moreau, A; Loup, B; Cooper, A; Van Manen, N (Ubiquity Press, 2019)
The enormous increase in digital spatial information has led archaeologists all over Europe to rely ever more on digital data to prepare and carry out archaeological research, both in academic and heritage management contexts. Spatial information is increasingly used to guide heritage management policies, from urban design to rural planning and tourism. Furthermore, spatial information is more and more employed to involve the general public, using digital technologies in museums and other places of archaeological interest, but also to involve amateur archaeologists in data collection programmes using crowdsourcing. With this proliferation of data and data use, issues of sustainability of digital data repositories, accessibility and reliability of data, standardization of data formats and management of property rights are currently widely debated inside and outside archaeology. However, they have not yet led to generally accepted practices of data management across or even within European countries. In this paper, we sketch the state-of-the-art of archaeological spatial data management, identify the major problem areas and reflect on potential improvements. We conclude that technical solutions are available, but will need a long-term transnational strategy in order fulfill the promise of open and sustainable spatial archaeological data for all user groups involved.